Solar radiation transmission in the canopy of Erythrina poeppigiana (Walpers) O.F. Cook - Nygren, Pekka; Maraux, Florent; Sánchez, Germán A. (Pesquisa Agropecuaria Brasileira, 1993)
A study was carried out to quantify the solar radiation transmission characteristics through the canopy of Erythrina poeppigiana (Walpers) O.F. Cook, a leguminous tree important in agroforestry systems of tropical America. The attenuation of the photosynthetically active radiation, measured in the form of the photosynthetic photon flux density (PPFD) was described applying the Beer's law, which empirically describes the radiation attenuation as a negative exponential function of the parth length of the solar beams through the tree canopy. The optical characteristics of the canopy, described by the PPFD transmission coefficient, had a cyclic variation in time, corresponding to the pruning cycle and the natural leaf fall. During a pruning cycle of 24 weeks the PPFD at the depth of one metre inside the canopy had the maximum value of 23.4% of the PPFD above the canopy, at 17 weeks from the pruning when the trees had a major leaf fall, and the minimum of 9.5% at the beginning of the sprouting after the pruning.
Keywords: agroforestry; Beer's law; canopy dimensions; photosynthetically active radiation; photosynthetic photon flux density (PPFD); sunflecks